Використання ультразвукових датчиків в мобільних роботах - Татарінцев, О. В. (ХНУРЕ, 2019)
The given work is devoted to the analysis of the work of ultrasound sensors in mobile works, the principle of operation of gauges is carried out. Ultrasonic sensors are elements that emit and receive sound waves when viewed from an object. Such sensors are commonly used for the needs of robotics, such as attaching to a mobile robot and connecting it to an Arduino board.
Keywords: Arduino; ultrasound sensors; mobil robots